Side effects of drugs annual. a worldwide yearly survey of new data in adverse drug reactions - Ray, Sidhartha D. (Side effects of drugs annual, 2019)
"Side Effects of Drugs Annual: SEDA is a yearly publication focused on existing, new and evolving side effects of drugs encountered by a broad range of healthcare professionals including physicians, pharmacists, nurse practitioners and advisors of poison control centres. This 41st on of SEDA includes analyses of the side effects of drugs using both clinical trials and case-based principles which include encounters identified during bedside clinical practice over the 12-14 months since the previous edition."-- Preface.